TNFAIP3 Facilitates Degradation of Microbial Antigen SEB in Enterocytes - Chen, Chi (Public Library of Science, 2012)
BACKGROUND AND AIMS: The enterocytes have the potential to absorb noxious substances, such as microbial products, from the gut lumen. How the enterocytes process the substances to harmless materials is not fully understood. This study aims to elucidate the role of ubiquitin E3 ligase TNFAIP3 (TNFAIP3) in facilitating the degradation of endocytic microbial products in enterocytes. METHODS: Human intestinal epithelial cell line, HT-29 cells, was cultured to monolayers using as an in vitro model to observe the endocytosis and degradation of microbial products, Staphylococcal enterotoxin B (SEB) in epithelial cells. The RNA interference was employed to knock down the TNFAIP3 gene in HT-29 cells to observe the role of TNFAIP3 in the degradation of endocytic SEB. The role of TNFAIP3 in facilitating the endosome/lysosome fusion was observed by immunocytochemistry. RESULTS: Upon the absorption of SEB, the expression of TNFAIP3 was increased in HT-29 cells. Silencing the TNFAIP3 gene in HT-29 cells resulted in a large quantity of SEB to be transported across the HT-29 monolayers to the transwell basal chambers; the transportation was via the intracellular pathway. TNFAIP3 was required in the fusion of SEB-carrying endosomes and lysosomes. CONCLUSIONS: TNFAIP3 plays a critical role in the degradation of endocytic SEB in enterocytes.